2012
DOI: 10.1021/ie200646p
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Some Macromolecules. Kinetics and Mechanism of Oxidation of Methyl Cellulose Polysaccharide by Permanganate Ion in Acid Perchlorate Solutions

Abstract: The kinetics of oxidation of methyl cellulose polysaccharide by acidic permanganate at a constant ionic strength of 2.0 mol dm −3 has been investigated, spectrophotometrically. Pseudo-first-order plots showed two distinct stages. The first stage was found to be relatively slow which corresponded to the formation of the substrate radical and Mn 3+ or Mn 4+ species as initial oxidation products, followed by an increase in the reaction rate at longer time periods. The reaction kinetics showed first-order dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…In view of the forgoing arguments and our interest in the oxidation of polysaccharides by various oxidants in both alkaline and acidic media [27][28][29][30][31][32][33][34] in particular by the alkaline hexacyanoferrate(III) as an oxidant [19][20][21] in a series of investigations in our laboratory, we are prompted to undertake the present investigation of oxidation of methyl ester of pectic acid (pectin) by alkaline [Fe(CN) 6 ] 3− with the aim to verify and rectify the errors in derivation of rate-law expression of this redox reaction, which is reported elsewhere, 26 as well as to elucidate a suitable oxidation mechanism consistent with the kinetic results obtained. Again, this investigation aims to shed some light on the nature of electron-transfer mechanism and transition states in the rate-determining step in comparison to that reported for oxidation of the other polysaccharides by this oxidant in alkaline solutions earlier.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the forgoing arguments and our interest in the oxidation of polysaccharides by various oxidants in both alkaline and acidic media [27][28][29][30][31][32][33][34] in particular by the alkaline hexacyanoferrate(III) as an oxidant [19][20][21] in a series of investigations in our laboratory, we are prompted to undertake the present investigation of oxidation of methyl ester of pectic acid (pectin) by alkaline [Fe(CN) 6 ] 3− with the aim to verify and rectify the errors in derivation of rate-law expression of this redox reaction, which is reported elsewhere, 26 as well as to elucidate a suitable oxidation mechanism consistent with the kinetic results obtained. Again, this investigation aims to shed some light on the nature of electron-transfer mechanism and transition states in the rate-determining step in comparison to that reported for oxidation of the other polysaccharides by this oxidant in alkaline solutions earlier.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators [8][9][10][11][12][13][14][15][16][17] have suggested that most of the oxidation reactions by permanganate ion in neutral and alkaline media proceed through intermediate complex formation between the oxidant and substrate. Spectroscopic evidence for such a complex was obtained from the UV-Vis spectra, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…All materials used were of analytical grade. A stock solution of the permanganate ion was prepared, stored, and standardized by the conventional methods described elsewhere . A stock solution of perchloric acid (HClO 4 ) was prepared from BDH‐grade perchloric acid of concentration 70% by weight, specific gravity = 1.66, and molarity = 11.6 in bidistilled water.…”
Section: Methodsmentioning
confidence: 99%
“…1 Therefore, it is extensively used as a good carrier polymer for drug delivery in medicine industry such as cancer-drug delivery and target diagnostics. 2 The kinetics and mechanisms of oxidation of natural polymers such as polysaccharides by the permanganate ion as a multivalent oxidant in both aqueous acidic 3 and alkaline 4 solutions was the subject of many investigators; a little attention has been paid to the oxidation of synthetic polymers such as poly(vinyl alcohol). 5 Indeed, the oxidation of PEG by the cerium(IV) ion as one-equivalent oxidant has been studied elsewhere.…”
Section: Introductionmentioning
confidence: 99%